2012
DOI: 10.1039/c2ra21214e
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the versatility of ring opening metathesis polymerization: an approach for gaining access to low density polymeric aerogels

Abstract: We report the preparation of low density polymeric aerogels using the ring opening metathesis polymerization (ROMP) approach to copolymerize dicyclopentadiene (DCPD) with norbornene-based monomers (NB-R) employing a first generation Grubbs' Ruthenium-based catalyst. The ROMP approach offers an attractive synthetic method that enables the fabrication of low-density (0.02-0.05 g/cm 3 ), uniform thickness aerogel coatings on non-planar substrates. First, we explore the effect of crosslinking in the polymer backbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Monomer 1 was synthesized following an adaption of previously published procedures . A mixture of Tosyl–Cl (9.2 g, 0.048 mol, 1.2 eq.…”
Section: Methodsmentioning
confidence: 99%
“…Monomer 1 was synthesized following an adaption of previously published procedures . A mixture of Tosyl–Cl (9.2 g, 0.048 mol, 1.2 eq.…”
Section: Methodsmentioning
confidence: 99%
“…The last decade has experienced an unprecedented growth of the types of aerogels available, ranging from inorganic [22][23][24][25] to organic (based on biopolymers [3,14,[26][27][28] and synthetic polymers) and hybrid inorganic-organic aerogels [29][30][31][32][33][34]. The growth of synthetic polymer aerogels in particular has been extremely rapid and now that class includes aerogels based on a wide variety of phenolic resins [35][36][37], polyamides [38][39][40], polyimides [41][42][43][44][45][46][47], polyurethanes [48][49][50][51][52][53], polyureas [54][55][56][57][58] and polymers derived via ring opening metathesis polymerization (ROMP) [42,49,[59][60][61][62][63][64]…”
Section: Introductionmentioning
confidence: 99%
“…It is considered as one of the most important synthetic tools in polymer and materials science and has been used for the industrial production of several commercial A wide variety of catalysts have been reported in the literature for the ROMP of DCPD. Most of those catalysts are based on mononuclear complexes of transition metals [59,61,[72][73][74], which can be catalytically active per se, or after activation with a co-initiator. Although less widely known, bimetallic clusters with metal-metal bonds have also been employed as ROMP catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In that regard, although there is a vast literature for monolithic aerogels derived from synthetic polymers, including aerogels based on phenolic resins (e.g., resorcinol-formaldehyde [19,55,56,57,58,59,60,61], polybenzoxazines [62,63,64,65,66], polyureas [67,68,69], polyimides [70,71,72,73,74], polyamides (Kevlar TM -like) [74,75,76], polyurethanes [77,78,79,80,81,82,83], as well as aerogels derived via Ring Opening Metathesis Polymerization (ROMP), including polynorbornene and polydicyclopentadiene [81,84,85,86,87], only a few examples of synthetic polymer aerogel particles are known, and they have become the subject of this mini-review. Those polymeric materials include mostly polyurea aerogels, and a few examples of polyimide and phenolic resin aerogels.…”
Section: Introductionmentioning
confidence: 99%